2018
DOI: 10.1186/s12929-018-0486-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensing acidosis: nociception or sngception?

Abstract: BackgroundSensing tissue acidosis is an important function of the somatosensory nervous system to response to noxious stimuli.Main bodyIn the pain clinic, acid or soreness sensation is a characteristic sensory phenotype of various acute and chronic pain syndromes, such as delayed onset muscle soreness, fibromyalgia, and radicular pain. However, soreness sensation is a sign of successful analgesia for acupuncture and noxipoint therapy. Thus, the nature of acid or soreness sensation is not always nociceptive (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…These ASIC1b-expressing DRG neurons with I ASIC were medium- to large-sized neurons with diameters ranging from 30 to 55 μm. The heterogeneity of the ASIC1b-expressing DRG neurons suggest that they might play multiple roles in different physiological and pathological contexts, because ASICs are proposed as dual-function proteins for acid- and mechanosensing (Cheng et al, 2018; Chuang et al, 2018; Lin et al, 2018). Especially, the expression of ASIC1b in large-diameter DRG neurons might implicate its role in proprioception similar to ASIC3 (Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ASIC1b-expressing DRG neurons with I ASIC were medium- to large-sized neurons with diameters ranging from 30 to 55 μm. The heterogeneity of the ASIC1b-expressing DRG neurons suggest that they might play multiple roles in different physiological and pathological contexts, because ASICs are proposed as dual-function proteins for acid- and mechanosensing (Cheng et al, 2018; Chuang et al, 2018; Lin et al, 2018). Especially, the expression of ASIC1b in large-diameter DRG neurons might implicate its role in proprioception similar to ASIC3 (Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Because ASICs can be activated in physiological pH ranges, ASICs seem to be the fine acid sensors involved in acidosis-induced muscle pain (Immke and McCleskey, 2001; Birdsong et al, 2010; Reimers et al, 2017). Reduced pH value in muscle tissue elicited by ischemic myalgia, inflammation, lesions, tumors or fatiguing exercise results in ASIC activation and nociceptive transduction (Cheng et al, 2018; Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ASIC3 is a voltage-independent sodium channel activated by the extracellular protons. It has been found as a molecular determinant involved in pain-associated tissue acidosis [58,59]. As well, a recent study showed that ASIC3 can detect extracellular acidification and also respond to mechanical stimuli [60,61].…”
Section: Sp-mediated Anti-nociception In Musclementioning
confidence: 99%
“…This effect is associated with opioid receptors activation [26]. There are also evidences that SP influences decrease of pain sensations in muscles by alterations in ion channels activity [27]. Our findings may suggest that increase of SP concentration contributes to pain sensations decrease, however further studies are necessary to verify this effect.…”
Section: Discussionmentioning
confidence: 50%